The Relationship of Endoscopic Proficiency to Educational Expense for Virtual Reality Simulator Training Amongst Surgical Trainees. Issue 7 (July 2015) - Raque, Jessica; Goble, Adam; Jones, Veronica M.; Waldman, Lindsey E.; Sutton, Erica
With the introduction of Fundamentals of Endoscopic Surgery™, training methods in flexible endoscopy are being augmented with simulation-based curricula. The investment for virtual reality simulators warrants further research into its training advantage. Trainees were randomized into bedside or simulator training groups (BED vs SIM). SIM participated in a proficiency-based virtual reality curriculum. Trainees' endoscopic skills were rated using the Global Assessment of Gastrointestinal Endoscopic Skills (GAGES) in the patient care setting. The number of cases to reach 90 per cent of the maximum GAGES score and calculated costs of training were compared. Nineteen residents participated in the study. There was no difference in the average number of cases required to achieve 90 per cent of the maximum GAGES score for esophagogastroduodenoscopy, 13 (SIM) versus 11 (BED) ( P = 0.63), or colonoscopy 21 (SIM) versus 4 (BED) ( P = 0.34). The average per case cost of training for esophagogastroduodenoscopy was $35.98 (SIM) versus $39.71 (BED) ( P = 0.50), not including the depreciation costs associated with the simulator ($715.00 per resident over six years). Use of a simulator appeared to increase the cost of training without accelerating the learning curve or decreasing faculty time spent in instruction. The importance of simulation in endoscopy training will be predicated on more cost-effective simulators.